(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3eMeO Hf eMeO Hf OGhhO bGjO GdMfaj s)
(3ChdgG (B:s
(3jHJOF ef GdQcf GdKGdK aj GdNhGJe s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B74 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B535s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B((3MOjK (B201) s
Keywords: (3GdMOjK h GdeUWdMs